2020
DOI: 10.1177/0269215520920333
|View full text |Cite
|
Sign up to set email alerts
|

Memory improvement in multiple sclerosis after an extensive cognitive rehabilitation program in groups with a multicenter double-blind randomized trial

Abstract: Objective: The aim of this study is to determine the effectiveness of an extended cognitive rehabilitation program in group’s sessions in multiple sclerosis. Design: Double-blind multicenter randomized trial. Participants: People with multiple sclerosis of 18 to 60 years, Expanded Disability Status Scale ⩽6.0, mild to moderate cognitive impairment. Interventions: They were randomized into cognitive rehabilitation program (ProCog-SEP) or in a placebo program. ProCog-SEP comprises 13 group’s sessions over 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…There were no significant differences in NP tests between the two groups. The three other studies showed some positive results [ 28 , 29 , 32 ]. The first study showed improvements in EM and EF tests, but this study did not identify a primary endpoint [ 28 ].…”
Section: Reported Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no significant differences in NP tests between the two groups. The three other studies showed some positive results [ 28 , 29 , 32 ]. The first study showed improvements in EM and EF tests, but this study did not identify a primary endpoint [ 28 ].…”
Section: Reported Resultsmentioning
confidence: 99%
“…This category includes five studies on memory rehabilitation [ 7 , 20 , 24 , 26 , 31 ] and three studies on several domains [ 16 , 20 , 34 ] ( Table 3 ). The rehabilitation was carried out by a research assistant or a trainer in four studies [ 14 , 31 , 32 , 38 ], a neuropsychologist in one study [ 9 ], speech therapists in one study [ 34 ], an occupational therapist in one study [ 27 ], and the therapist was not specified in one study [ 20 ]. The material used was generally written material, but it could include computer-assisted exercises (three studies) [ 20 , 31 , 34 ].…”
Section: Reported Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of psychological and psychiatric specialists and teamwork for the proper management of MS patients is also called for. This is of exceptional importance, as many of the factors that we have shown to play a major role in determining the patients' HRQoL have been demonstrated to be ameliorated and managed by not only a psychopharmacological but by a psychotherapeutic approach as well[103,107,131].…”
mentioning
confidence: 99%